Effects of creatine monohydrate supplementation during combined strength and high intensity rowing training on performance - Syrotuik, D. G.; Game, A. B.; Gillies, E. M.; Bell, G. J. (Canadian Journal of Applied Physiology, 2001)
This study investigated the effect of creatine monohydrate (Cr) supplementation on performance and training volume in rowers. Twenty-two rowers trained with continuous and interval rowing and resistance training 4 and 2 days/week, respectively, for 6 weeks. Cr supplementation consisted of a 5-day load (0.3 g/kg-1\mult\ day-1) followed by a 5-week maintenance dose (0.03 g/kg-1\mult\ day-1) while training. Five days of Cr loading did not change body composition, repeated interval rowing performance, 2,000-m rowing times, or strength performance. Five additional weeks of training with a maintenance dose of Cr or placebo significantly improved body composition, \dvØ2max, 2,000-m rowing times, repeated power interval performance, and strength to a similar extent in both groups. Subjects training with Cr did not perform more repetitions per set of strength exercise nor produce or maintain higher power outputs during repeated rowing sessions. Cr supplementation did not increase performance or training volume over a placebo condition in rowers that performed a combined high intensity rowing and strength program. .Canadian Journal of Applied Physiology, 26 (6).